Agrarian Marxism and the proletariat: a palm oil manifesto. Issue 4 (7th June 2021) - Pye, Oliver
ABSTRACT: This article attempts to re-integrate a Marxist perspective of the collective agency of the proletariat into the analysis of the corporate food regime. The article first summarises Marx's key ideas on the proletariat and then discusses their relevance for capitalist agriculture today, arguing that labour makes up an important part of the contested social relations of production in contemporary agrarian capitalism. Drawing on ongoing empirical research with plantation workers and labour activists in Indonesia and Malaysia, it then appraises the current state of class struggle in the palm oil sector, arguing that it is characterised by everyday class struggles and an emerging trade union movement. The article concludes – and this is the 'manifesto' element – by suggesting that a reorientation towards labour in the 'agrarian question' could overcome some of the limitations of the food sovereignty movement and open up new perspectives for the social-ecological transformation of capitalist agriculture.